Two sides of the same coin: Meta-analysis uncovered the potential benefits and risks of traditional fermented foods at a large geographical scale - Xu, Meng; Su, Shunyong; Zhang, Zeng; Jiang, Shuaiming; Zhang, Jiachao; Xu, Yanqing; Hu, Xiaosong (Frontiers in Microbiology, 2022)
Traditional fermented foods, which are well-known microbial resources, are also bright national cultural inheritances. Recently, traditional fermented foods have received great attention due to their potential probiotic properties. Based on shotgun metagenomic sequencing data, we analysed the microbial diversity, taxonomic composition, metabolic pathways and the potential benefits and risks of fermented foods through a meta-analysis including 179 selected samples, as well as our own sequencing data collected from Hainan Province, China. As expected, raw materials, regions (differentiated by climatic zones) and substrates were the main driving forces for the microbial diversity and taxonomic composition of traditional fermented foods. Interestingly, a higher content of beneficial bacteria but a low biomass of opportunistic pathogens and antibiotic resistance genes were observed in the fermented dairy products, indicating that fermented dairy products are the most beneficial and reliable fermented foods. In contrast, despite the high microbial diversity found in the fermented soy products, their consumption risk was still high due to the enrichment of opportunistic pathogens and transferable antibiotic resistance genes. Overall, we provided the most comprehensive assessment of the microbiome of fermented food to date and generated a new view of its potential benefits and risks related to human health.